CARBON PASTE ELECTRODE MODIFIED WITH TIO2 AND MOLECULARLY IMPRINTED POLY(METHYL RED) FOR DETERMINATION OF ASCORBIC ACID BY VOLTAMMETRIC METHODS - Arwinda Filzahimka, Roro
Ascorbic acid (AA) has an important role in the human body, including as an antioxidant that effectively overcomes free radicals and maintains the body's metabolic function through oxidation and reduction reactions. AA deficiency can lead to immune system disorders, higher susceptibility to infections, joint pain and canker sores. While excessive consumption of AA can increase the absorption of iron in the body, so that levels become too high and can cause kidney stone disease, allergies, heart problems, blood thinning, and kidney failure. Thus, the consumption of AA by the body must be in a certain amount, so an analytical method is needed to determine AA levels. In this study, a voltammetric method was developed to determine AA using a carbon paste electrode (CPE) as a working electrode. CPE was chosen because it has good conductivity and a large active surface area. In this study, CPE performance was improved by modifying it with TiO2 and red polymethyl imprinted with AA molecules. This modification is used to increase the sensitivity of the measurement to AA. TiO2 is a semiconductor compound commonly used for oxidation and reduction of inorganic and organic species. TiO2 has a very high surface to volume ratio and a large surface area. Polymethyl red has been used as a moldless polymer to analyze various compounds. The results showed that the optimum modification of CPE with TiO2 was obtained by dripping TiO2 as much as 10 ?L on the surface of CPE. CPE that has been modified with TiO2 is then electropolymerized with cyclic voltammetry technique as much as 20 cycles with a composition of AA: methyl red by 1: 1 mM. The selection of optimum conditions is based on the performance of the electrode that has the highest peak current value when used in AA measurements with a certain concentration. The optimum measurement conditions were obtained in pH 4 solution using square wave voltammetry technique. The determination of electrode performance is seen from the repeatability of AA measurements using 1 CPE (relative standard deviation 2.59) and the repeatability of making 3 CPE (relative standard deviation 3.3). Analysis of the scan rate shows that the process occurring on the electrode surface is controlled by the diffusion process. The measurement work area is in the range of 0.001 ? 0.01 mM with a gradient value of 47.576. The detection limit is 0.6999 ?M. Measurements of ascorbic acid samples from commercial products showed a recovery of 95.2% by voltammetric method, while by UV ? Vis spectrophotometry method by 70.45%. Voltrammetry method can be said to be better than UV ? Vis spectrophotometry method in ascorbic acid measurement in commercial samples.